Sensorless vector control of surface mounted permanent magnet machines without restriction of zero frequency - Silva, César Armando (2003)
Permanent magnet motors have a series of characteristics that make them attractive for the use in industrial drives: low maintenance, high dynamics, small size and mass to power ratio. In particular its higher efficiency means that permanent magnet synchronous motors may be used instead of electro-magnetically exited motors (such induction machines or commutator DC motors) in applications where the energy savings compensate the higher initial cost. Nevertheless, the need for a shaft mounted position measurement to perform the orientation of the control of the synchronous machine is of concern, because it increases the total drive cost and reduces reliability.